2014
DOI: 10.4149/bll_2014_006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficiency of resistant hypertension in cardiologist’s office

Abstract: Background: The target values of blood pressure have not been achieved in our population of patients suffi ciently. The most diffi cult is a control of patients with resistant hypertension. We do not have data about effi ciency treatment of these patients today.Objectives: The aim of our study was to assess current treatment status and by antihypertensive treatment modifi cation we tried to reach an adequate blood pressure control. Methods: Fifty two patients suffering from resistant hypertension 2-3 degree ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Obesity (body mass index ≥ 30 kg/m 2 ) was present in 51.8 % of patients, current smoking in 7.0 % and smoking history in 27.2 %. Diabetes mellitus was present in 54 %, ischemic heart disease in 64.9 %, previous myocardial infarction in 13 Values are mean±SD, SBP -systolic blood pressure, DBP -diastolic blood pressure, HR -heart rate, SD -standard deviation, ARV -average real variability Tab. 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity (body mass index ≥ 30 kg/m 2 ) was present in 51.8 % of patients, current smoking in 7.0 % and smoking history in 27.2 %. Diabetes mellitus was present in 54 %, ischemic heart disease in 64.9 %, previous myocardial infarction in 13 Values are mean±SD, SBP -systolic blood pressure, DBP -diastolic blood pressure, HR -heart rate, SD -standard deviation, ARV -average real variability Tab. 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, non-dipping was found to be more common in the RH patients. In the RH patients, recovery of pathological diurnal rhythm was associated with an improved BP control (13). Moreover, non-dipping is known to be associated with the target organ damage (17), cardiovascular events and mortality (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The renin-angiotensin-aldosterone system (RAAS) is the main regulator of sodium and fl uid balance, and one of the major mechanisms involved in the pathogenesis of hypertension. Dual blockade of the RAAS with mineralocorticoid receptor antagonists, specifi cally spironolactone, in combination with an ACE inhibitor or ARB, is now routinely commonly used to treat RH (24,25,26).…”
Section: Tab 2 Signs and Symptoms That Suggest Specifi C Causes Ofmentioning
confidence: 99%